Entre estrelas e hyperlinks : uma leitura de 88 Constellations for Wittgenstein (to Be Played with the Left Hand), de David Clark - Silveira, Alice Garcia (2019)
This research aims to analyze 88 Constellations for Wittgenstein (to be Played with the Left Hand), by David Clark (2010). Cyberliterature, which comprises 88 Constellations, is still understudied in Brazilian academy, and is yet mainly unknown by general public. That is why Chapter 1 conceptualizes and contextualizes cyberliterature, by means of different of works from different periods since its creation. Before presenting the thematic pathways analyzed in David Clark’s work, Chapter 2 brings a structural analysis of 88 Constellations, as well as Ludwig Wittgenstein's short biography, and a presentation of his book Tractatus Logico- Philosophicus (2010), which were used as cornerstone for the analysis herein made. The thematic pathways analyzed in this thesis are Ludwig Wittgenstein and his Tractatus, the Hand, and the Double. Pervaded by knowledge of all kinds, 88 Constellations for Wittgenstein puts the reader in touch with visual arts, music, cinema and photography, as well as presents playful and poetic reflections on philosophy, logic and language. Therefore, 88 Constellations contains what is necessary to constitute Mathesis, a characteristic mentioned by Roland Barthes (1970) as one of the three functions of literature.